PENGARUH MOTIVASI BELAJAR TERHADAP PENGAMBILAN KEPUTUSAN KARIR MAHASISWA AKOMODASI PERHOTELAN - Ribka; Nurlaila Mashabi; Elmanora (Family Welfare Education, 2022)
This study aims to analyze the influence of learning motivation on student career decision making. Respondents in this study were 51 Hospitality Accommodation students in the Family Welfare Education Study Program, Jakarta State University. Sampling using saturated sampling technique. The research method used is a quantitative method. The results showed that the influence learning motivation on decision making is a significant influence and indicate that an increase in learning motivation can improve career decision making in students. Keywords: career decision making, learning motivation